PROBLEMS OF ENFORCEMENT OF CERTAIN LEGAL PROVISIONS IN TRANSPLANTOLOGICAL PRACTICE AND SOLUTION APPROACHES - S. V. Gautier; S. M. Khomyakov (Вестник трансплантологии и искусственных органов, 2016)
Aim. To carry out the analysis of enforcement of regulatory legal acts in transplantological practice, to specify the existing gaps and collisions in them, and to offer approaches for its elimination. Materials and methods. The legislation of the Russian Federation in the fi eld of donation and organ transplantation and(or) tissues (an information law system «Garant»). Archive of addresses to the chief transplantologist of the Russian Ministry of Healthcare concerning application of certain precepts of law in transplantology since 2009 till present. Results. Legislative and subordinate acts relating to the area of donation and organ transplantation and(or) tissues are studied; addresses to transplantologies regarding application of certain law precepts are analyzed. Conclusion. Legislative and subordinate acts in force in the fi eld of donation and organ transplantation and(or) tissues contain gaps and collisions which interfere with the work and development of the industry. With respect thereto, it is reasonable to make amendments eliminating legal defects to a number of regulatory legal acts: to the Federal law No. 323-FZ, to the Act of the Russian Federation No. 4180-I, to the Resolutions of the Government of the Russian Federation No. 291 and No. 294, to the Orders of the Ministry of Healthcare of the Russian Federation No. 567n, No. 307n/4, No. 355n.